Why manage noncrop biodiversity - Korkaric, M.; Beed, Fenton D. (2010)
This paper focuses on the management of non-crop biodiversity, conservation and use of non-plant taxa and its future challenges and opportunities. The collection, conservation and sustainable use of insects and mites, fungi, bacteria, viruses and nematodes that are either beneficial or antagonistic to crops are also pointed out.